Influence of secondary forest succession on plant diversity patterns in a Mediterranean landscape. (2nd August 2013) - Amici, Valerio; Santi, Elisa; Filibeck, Goffredo; Diekmann, Martin; Geri, Francesco; Landi, Sara; Scoppola, Anna; Chiarucci, Alessandro; Vetaas, Ole
Abstract Aim As a consequence of multiple cycles of deforestation and reforestation, most forest landscapes in Europe consist of a complex mosaic of patches of different successional ages. Despite the biogeographical distinctiveness of the Mediterranean region, studies on the effects of forest age on plant species diversity and composition are almost lacking for this area. This paper evaluates the influence of forest successional age on plant species richness and composition in various forest types of Mediterranean Italy. Location The Natura 2000 network of Siena Province, Tuscany, Italy. Methods Occurrence data on vascular plant species in 208 forest plots were obtained from a larger data set sampled with a stratified random design. The forest successional age of each plot was quantified through a series of historical maps. Species richness and composition were related to the age of the forest by means of GIS techniques and univariate and multivariate statistical analyses. Results Total species richness markedly decreased with increasing successional age due to a significant decrease in the richness of open‐habitat species which was not matched by increasing richness of mature forest species. Successional age was the key factor in controlling species richness, while local environmental properties emerged as the main factors shaping community composition. The different forest types showed different temporal trends of species richness and composition and different hierarchies of explanatory factors. Main conclusions Forest successional age emerged as an important factor affecting both species richness and composition, even within the same forest type. Thus, the classification and prioritization of Mediterranean forests exclusively based on present physiognomy or environmental variables causes loss of information about species richness and composition; this could be detrimental for biodiversity conservation.